ANALISIS YURIDIS PERJANJIAN TERTUTUP BERDASARKAN UNDANG-UNDANG PERSAINGAN USAHA - Werner Wada Betu; N.G.N Renti Maharaini (Fakultas Hukum Universitas Trisakti, 2022)
AHASS workshop owners are required by the terms of the agreement between PT AHM and the Main dealer and Dealer to accept and purchase other products and services from PT AHM. The issue is whether PT AHM's efforts to enter into closed agreements with Main Dealers and Dealers in Indonesia constitute violations of Article 15 paragraphs 2 and 3 of the Business Competition Law and whether the Rulle of Reason approach, which was employed in KPPU's decision No. 31/KPPU-I/2019, was appropriate in determining such violations. The research is descriptive-analytical in character, employs normative research methodology, uses primary and secondary data kinds, descriptive-qualitative data analysis and deductive reasoning to reach results. Results of the study of the Business Competition Law, Article 15 guidelines, and other related regulations led to the following discussions, findings, and conclusions: PT AHM may enter into an agreement with the Main Dealer, but the agreement may not contain a tying clause or a vertical agreement on discount. Additionally, because the agreement has a negative effect, it is required to use the per seillegal method while proving a closed agreement.